2003
DOI: 10.1002/hup.487
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein and depressed mood in a sub‐group of smokers during nicotine abstinence

Abstract: Cigarette smokers frequently fail multiple attempts to quit smoking, often because of the unpleasant symptoms that accompany quitting. Similar unpleasant symptoms accompany inflammatory responses during infection and autoimmune disease. The hypothesis that smoking abstinence induces inflammation was tested. Eighteen smokers (n = 18) were evaluated while smoking freely and after 24 h of nicotine abstinence. Immune, cardiovascular and psychological measures were collected. Hunger, nervousness, anxiety, restlessn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Moreover, since C reactive protein is an inflammation marker evaluated to predict several cardiovascular diseases [32], the direct effect of nicotine on this protein may mask in smokers the increased cardiovascular risk associated with smoking. A modification in C-reactive protein levels was detected in humans also during abstinence, although with a split response [33].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, since C reactive protein is an inflammation marker evaluated to predict several cardiovascular diseases [32], the direct effect of nicotine on this protein may mask in smokers the increased cardiovascular risk associated with smoking. A modification in C-reactive protein levels was detected in humans also during abstinence, although with a split response [33].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that CRP and SAA level are elevated in cocaine abusers, alcohol users and cigarette smokers [19,20,29]. The inflammatory markers CRP and SAA proteins play a major role in chronic inflammation of HIV infection, inducing immune dysfunction, disease progression and subsequently decreased CD4 count [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although tocilizumab has similar efficacy and safety profiles to TNF-α inhibitor for RA treatment, our mechanism suggests that IL-6 and TNF-α act through different pathogenic mechanisms in RA and other inflammatory diseases [19,20]. Actually, studies have reported that increased CRP and SAA levels in alcohol users, abusers of cocaine and methamphetamine (METH), cigarette smokers and HIV-infected patients [21][22][23][24]. It has been well known that alcohol user and drug abusers develop chronic inflammation that leads to immune Citation: Song SNJ, Yoshizaki K (2016) Mechanism and Clinical Significance of IL-6 Combined with TNF-α or IL-1 for the Induction of Acute Phase Proteins SAA and CRP in Chronic Inflammatory Diseases.…”
Section: Clinical Significance Of Il-6 Combined With Il-1 or Tnf-α Inmentioning
confidence: 83%